FINANCIAL HIGHLIGHTS COMPARISON OF THE PHARMACEUTICAL INDUSTRY BEFORE AND DURING THE PANDEMIC PERIOD : 2018-2021 ANALYSIS - Lestari, Tri; Damhudi, Dedi; Rastryana, Ulta; Rusmayanti, Santi (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2023)
During the COVID-19 pandemic, the pharmaceutical industry became a priority sector for the government's efforts towards achieving the Making Indonesia 4.0 program. This priority was driven by the increased demand for supplements, vitamins, and medications to boost immune systems. Unlike other sectors that experienced a decline in demand during the COVID-19 pandemic, the pharmaceutical industry saw an upward trend. This presents an interesting opportunity to assess the financial performance of these pharmaceutical companies. The objective of this assessment is to determine whether there are any differences in financial performance between the pre-pandemic and during the pandemic periods (2018-2021) in the pharmaceutical industry. The study involved a sample of 10 pharmaceutical companies listed on the Indonesia Stock Exchange, including both state-owned enterprises (BUMN) and private companies. The assessment method employed was the non-parametric Mann-Whitney test, as the available data did not follow a normal distribution. The research findings indicate that the Current Ratio (CR), Net Profit Margin (NPM), Debt to Asset Ratio (DAR), and Debt to Equity Ratio (DER) showed no significant differences between the pre-pandemic period (2018-2019) and during the COVID-19 pandemic period (2020-2021).